The Effect of the Bio-Extract of Bacteria Bacillus Subtilis & Pseudomonas Fluorescence on the Tomato - Saleh, Ban Star; Attia, Wesal Ali; alwahed, Ali Ahmed abd; Karim, Mustafa Nabil (American Journal of Biology and Natural Sciences, 2025)
This study includes the possibility of producing a biological product from the two strains of Bacillus and Pseudomonas bacteria, with the aim of using and circulating it economically and in commercial scope by the beneficiaries in the country after determining the basic elements for the production of the preparation represented by the fermentation medium which is selfishly composed of the extract of rennet. Our test results. Is that the wheat extract acts as a fermentation medium and also increases the density of bacteria. When testing the substance Caco3 as a carrier of the biological product, calcium carbonate showed a higher efficiency than the corrosion, as the density of bacteria increased by loading them with calcium carbonate, while it decreased and by a small percentage when using talc as a substance. Haha, the case of Ki. The results of the experiment showed the ability of the biological product to give high rates of growth as it increased The dry and fresh weight of tomato foliage, and the average dry weight of tomato plant when treated with the preparation was 0.24 g germination when using 8 g / 100 g seeds. The lean weight of tomato plants, using a concentration of 8 g / 100 gm of tomato seeds, increased to 1.8 g.